Pengabaian Nafkah sebagai Delik Pidana: Analisis Maqaṣid Syariah - Muhammad Nasir (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study analyzes the neglect of maintenance as a criminal offense from the perspectives of Islamic law and Indonesian positive law using a maqāṣid al-sharī‘ah approach. The main issue lies in how neglect of maintenance is positioned as a legal violation affecting the protection of family members’ rights, particularly women and children. This research employs a library-based method with a qualitative approach through normative and conceptual analysis of legal regulations and Islamic legal literature. The findings reveal that neglect of maintenance is not only a violation of family obligations but can also be classified as a form of economic domestic violence with criminal consequences. From the maqāṣid al-sharī‘ah perspective, such actions contradict the fundamental objectives of Islamic law, especially in protecting life, lineage, and property. Therefore, the criminalization of maintenance neglect is relevant in promoting justice and victim protection. This study highlights the importance of integrating criminal law, restorative approaches, and Islamic values to establish a more just and welfare-oriented legal system.